NATURAL COLOURANTS: A REVIEW (International Association of Biologicals and Computational Digest, 2023)
Natural materials like plants, animals, minerals, insects, bacteria, and fungi can be used to make natural dyes, but the majority of dyes are derived from plant components like leaves, bark, flowers, fruits, and roots. Natural dyes have some unique qualities, such as calming colors, biodegradability, safety, non-hazardousness, antimicrobial resilience, biodegradability, etc. Plant parts and occasionally their by-products are needed as raw materials in the extraction procedure for natural dyes (Iqbal & Ansari, 2021). Many different things have been colored with natural dyes, including leather, fur, silk, cotton, wool, and other natural materials (Cristea & Vilarem, 2006).
Keywords: Natural dye, Sources, History, Application